2021
DOI: 10.1002/hyp.14167
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of permeable interlocking concrete pavement on the runoff hydrograph: Volume reduction, peak flow mitigation, and extension of lag times

Abstract: Permeable pavements are implemented to provide at-source treatment of urban stormwater runoff while supporting vehicular and pedestrian use. Studies on these systems have mainly focused on those treating only direct rainfall and installed atop well-drained soils which typically provide substantial hydrologic mitigation through exfiltration that may not be representative of more hydrologically taxing conditions.A single lane parking area retrofitted with permeable interlocking concrete pavement in Vermilion, OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…It showed that when the rainfall interval was short, the material of the leveling layer had a greater influence on the runoff control rate. This trend also occurred because the previous rainwater was retained in the pavement, and the infiltration capacity was reduced, which shows consistency with other research findings [40,41]. Compared with natural sand and gravel, the medium sand had a stronger water holding capacity, and it took longer to empty the rainwater [11,41].…”
Section: Runoff Control Ratesupporting
confidence: 88%
See 1 more Smart Citation
“…It showed that when the rainfall interval was short, the material of the leveling layer had a greater influence on the runoff control rate. This trend also occurred because the previous rainwater was retained in the pavement, and the infiltration capacity was reduced, which shows consistency with other research findings [40,41]. Compared with natural sand and gravel, the medium sand had a stronger water holding capacity, and it took longer to empty the rainwater [11,41].…”
Section: Runoff Control Ratesupporting
confidence: 88%
“…Compared with natural sand and gravel, the medium sand had a stronger water holding capacity, and it took longer to empty the rainwater [11,41]. Future research work could consider various other factors, such as land use patterns, soil type, topography, runoff quality and quantity, and contamination in nearby water resources, along with pavement design and possible filler materials [5,11,12,29,[38][39][40][41][42]. The findings of the current study provide an opportunity for the successful implementation and beneficial use of permeable pavements based on the local urban environment and land use pattern, and climatic, geological, and hydrologic conditions.…”
Section: Runoff Control Ratementioning
confidence: 99%
“…objectives of hydrological performance typically focus on quantifying the volume and peak flow reduction [29,[33][34][35][37][38]. Table 3 summarizes the details of the pavement characteristics and methodologies adopted for evaluation of the hydrological performance.…”
Section: Researchmentioning
confidence: 99%
“…A vazão de pico do hidrograma de projeto representa a maior vazão instantânea que irá passar no exutório da bacia. O aumento da área permeável, ou sua presença, em caixas de via é capaz de reduzir a vazão de pico, devido a capacidade de infiltrar e evapotranspirar a água ( TIRPAK et al, 2021). Estudando uma bacia que possui 57% da área impermeabilizada, Mesquita e Lima Neto (2020), identificaram que um aumento de 20% das áreas de infiltração resultou em uma redução de 12% na vazão de pico.…”
Section: Sem Jardim De Infiltraçãounclassified